Photogrammetry based characterization of hydro-mechanical properties of a rock fracture. Issue 1 (August 2021) - Torkan, M; Uotinen, L; Nieminen, V; Rinne, M
Abstract: Hydro-mechanical properties of a single fracture are governed by several parameters such as contact area, roughness, tortuosity, aperture, channeling, matedness, sample sizes, normal stress, flow regime, and flow boundary conditions. In this study, photogrammetry with numerical modeling and laboratory measurements were used to investigate the influences of roughness, normal stress, aperture, water pressure, and different flow boundary conditions on fluid flow in an artificial granite fracture. A Finnish Kuru grey granite block was mechanically split, and a 250 mm × 250 mm × 100 mm slab pair sample with a tensile crack in the middle was extracted. A photogrammetry-based method was used to reconstruct a 3D model of the fracture geometry. The resulting model was numerically simulated with COMSOL using the Navier-Stokes equations. Fluid flow experiments were computed with the Forchheimer equation. Comparison between the numerical modeling results and the analytical solution confirms that the 3D roughness geometry has a crucial role in defining the transmissivity, especially for nonlinear flow. On the other hand, normal stress increases fracture closure and increases contact areas, decreasing the hydraulic aperture and changing the flow paths. The presented method can be used in the contactless estimation of fluid flow properties of rock joints.